Judiciarisation des personnes itinérantes à Québec : une géographie des pratiques policières répressives au service de la revitalisation - Catherine Chesnay; Céline Bellot; Marie-Ève Sylvestre (EchoGéo)
The occupation of public spaces by homeless people is increasingly controlled and repressed by public and private police in several Western cities. This penalization of homeless people is in part connected to changes in urban policies, transformations in community policing strategies and practices but also to socio-spatial gentrification issues.. As cities compete to be ever more prosperous, dynamic, attractive and rich, they try to make poverty invisible. Our study on the penalization of homeless people in various Canadian cities fits in this broader context of penalization of poverty and homelessness. The purpose of this paper is to show how the spatialization of police repressive practices are linked to the revitalization of certain neighborhoods in Quebec City by considering where tickets have been issued to homeless people.